2012
DOI: 10.1097/bsd.0b013e318260dd0b
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Surgical Experience on the Efficiency of Discectomy in TLIF

Abstract: Our results demonstrate that a satisfactory discectomy may be performed by surgeons with relatively less surgical experience in the transforaminal approach using a powered discectomy device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Pumberger et al, in two separate cadaveric studies, also found that the posterior contralateral quadrant was the most difficult disc quadrant to prepare in a unilateral TLIF [14,15]. Although there was no difference in disc removed from the anterior ipsilateral quadrant compared with the posterior ipsilateral quadrant in the open approach, the MIS approach was slightly less effective at removing disc from the anterior ipsilateral quadrant compared with the posterior ipsilateral quadrant.…”
Section: Discussionmentioning
confidence: 96%
“…Pumberger et al, in two separate cadaveric studies, also found that the posterior contralateral quadrant was the most difficult disc quadrant to prepare in a unilateral TLIF [14,15]. Although there was no difference in disc removed from the anterior ipsilateral quadrant compared with the posterior ipsilateral quadrant in the open approach, the MIS approach was slightly less effective at removing disc from the anterior ipsilateral quadrant compared with the posterior ipsilateral quadrant.…”
Section: Discussionmentioning
confidence: 96%
“…Pumberger et al, in 2 separate cadaveric studies, also found that the posterior-contralateral quadrant was the most difficult disc quadrant to prepare in a unilateral TLIF. 7,8 The study by Rihn et al had a substantially better endplate preparation rate than the current study, reporting an overall endplate preparation rate of 73% by surface area. 9 Our results were more consistent with those reported by Tatsumi et al, 10 who found a much lower preparation rate of 39.2% that was more consistent with our study.…”
Section: Discussionmentioning
confidence: 44%
“…Microscopic observation indicated that the veins around the nerve roots were well protected or coagulated, which further prevented blood loss. Therefore, blood loss in MMI-TLF patients (42 ml) was reduced, in comparison with values reported for MI-TLIF (81.5 ml) [26]. This represents an advantage over MI-TLIF and should be further explored in future studies.…”
Section: Resultsmentioning
confidence: 73%